(untitled) (Research, Society and Development, 2023)
The aim of this study is to evaluate the effectiveness of using Aloe vera in the healing process. It was necessary to search for data in MedLine and LilaCS electronic databases, using the descriptors for indexing scientific articles Health Sciences Descriptors (DeCS): “Aloe vera”, “healing” and “aloe vera”. After applying the inclusion criteria, seven scientific articles were used in this review. Teplick et al. (2018) shows that Aloe vera had significant stimulatory effects on cell proliferation and migration of fibroblasts and keratinocytes. Surprisingly, aloe vera also exhibited strong protective effects on preservative-induced keratinocyte death. However, few studies have examined the antioxidant capabilities of Aloe vera plants during different growth periods, and there are few clinical trials and in vitro studies that show this bioactive potential. About the effectiveness of Aloe vera popularly known as aloe in the healing process, there is still a lack of more robust scientific evidence proving such potential.